Anthracycline induced cardiotoxicity: biomarkers and "Omics" technology in the era of patient specific care. Issue 1 (10th May 2017) - Moazeni, Shayan; Cadeiras, Martin; Yang, Eric H.; Deng, Mario C.; Nguyen, Kim‐Lien
Abstract: Anthracyclines are highly effective against a variety of malignancies. However, their dose‐dependent cardiotoxic effects can potentially limit their use. In the past decade, serum biomarkers have been used to diagnose, monitor, predict, and prognosticate disease. Biomarkers such as cardiac troponin and natriuretic peptides have some predictive value, but still lack reliability in this patient population. Novel biomarkers such as galectin‐3, soluble ST‐2 proteins, myeloperoxidase, and fibrocytes are being explored as potential biomarkers to reliably predict the onset of cardiotoxicity. Leveraging multiomics technology to map highly sensitive biomarkers in an integrated approach through pattern deconvolution may better define those at highest risk of developing cardiotoxicity and further the goal of precision medicine. In this work, we aim to provide a brief overview of traditional serum biomarkers, summarize current investigations on novel circulating biomarkers, and discuss a systems‐based approach to anthracycline‐induced cardiotoxicity through "omics" technology.